A Sociological Study of the Consequences of Double Agency and Maximizing Profits in Pyramid Companies, a Critical Ethnography - Soheyla Hajiheidari,; Ali Ruhani (پژوهش‌های راهبردی مسائل اجتماعی ایران, 2019)
Introduction The world is pace with the processes of globalization. Iran is not apart from this globalizing process and has been involved in many trends, including the phenomenon of pyramid companies (network marketing). This issues a new style of modern business, with its new work in the late of 70s Hijri (or in the early 80s) with companies such as Goldquest and Goldmine in Iran. Their activities created very crucial negative effects to the public, the community and economic body of the country and made a constitutional crisis in the country’s atmosphere. Finally, the discretion of the legal authorities banned their activities in the country. The business, however, is now a few years with a new light in the face by removing the same obstacles in the country with a legal permit. While the country’s current state is worse than the previous decade (80s) in terms of economic difficulties, the sharp recession, the problems of country’s active population and thousands of fundamental problems whose main origins go back to the economy. On the other hand, it is expected that this kind of trade problems and barriers in the past and may be solved to a great extent, but we are witnessing difficulties and obstacles. The high rate of the young population of the country has been mentioned in recent years by the social sciences thinkers. According to the demographic theory of open window of population, Iran is a highly sensitive site in the region as well as inside the country due to its young population, that, if taken in the right direction, it would promote the country and otherwise damage. This high percentages, despite university education, face a demographic inflation of youth by failing to attract the labor market. Based on different studies, they report a high percentage of frustration, depression, and so on. On the other hand, in recent years, we see major changes in the values and attitudes of Iranian youth for different reasons, including the growth and development of communication and technologies. Thus, the characteristics of social context in Iran have different forms of development for boosting networks. The prevalence of globalization and its ideology, the sudden rise of population and unemployment, social networks, and strong local regions (derived from pre modern times) have all contributed to the prevalence of pyramid-based enterprises (network marketing), which have the slogan of acquiring huge fortunes in a short period of time: This study investigates how profit maximization strategies are implemented in pyramid companies and what the consequences of these strategies are.   Material & Methods The paradigm used in this study is critical ethnography and research is done using qualitative methodology. The critical ethnography has been chosen by the 5-scale approach of Carspecken. Sampling is based on purposive and chain sampling. In this direction, after participatory hidden observation and semi structured interviews with the active members in the companies, 16 cancelled individuals were selected from 3 network marketing companies to do deep interviews to achieve theoretical saturation.   Discussion of Results & Conclusions The result indicate that pyramid companies are able to attract a large number of people in Iran through the use of credit over a very long period of time. In this way, compliant and reagent credits are key factors that these companies use to obtain their own purposes. Pyramid companies are trying to change the style of business and create a fundamental shift in the field. But, they try to achieve their goals by exploiting the traditional market failures and variables involved in the traditional world. The actors involved in these enterprises are usually from poor levels of the society who have little economic and social power. In particular, class categories include the middle and lower classes which are relatively marginalized in the society and are constantly suppressed by various social, political, and economic forces. In such circumstances, these people usually have a neutral agency. Iran as a polarized society has suffered extensive social damage due to its policy of adjustment and corruption resulting from this issue (Piran, 2004: 24) which has caused to attract a particular context of modern commerce. People on the margins are also influenced by the positive advertisements of this emerging systems, and tend to identify their own identity as a networking one and rebuilt their existing ruined and suppressed identity. It is at this point that agents’ state of mind at modern tribes change (confronting with reality). They have to limit many areas of their lives to gain profits, therefore, separation of family, lack of intimacy with wife, borrowing money and etc. are damages that are imposed on them. This process is moving forward that in the face of structure, the functionality of the actors is weak and defeated, and eventually leads to the withdrawal of the membership from the system.